DESCRIPTION OF STUDENTS' ACADEMIC STRESS LEVELS IN COMPLETING THEIR FINAL THESIS ASSIGNMENTS AT THE FACULTY OF MEDICINE AND HEALTH SCIENCES UNIVERSITAS JAMBI - Marta, Marta Prima Yuda; Indah Mawarti; Muthia Mutmainnah (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Stress academic is condition student faced with with a demands academics who are not capable overcome with Good so that can bother smoothness academic. Thesis is one of demands academic Where Lots student experience stress academic. Prevalence students who experience stress academics in Indonesia amounted to 36.7-71.6%. Research This aiming For know description level stress academic student in finish task end thesis at the Faculty Medicine and Health Sciences, University of Jambi. Type study This is study descriptive quantitative use technique cluster random sampling with amount sample as many as 97 students faculty medicine and science health class of 2019. Instruments used is Student-life Stress Inventory. Data analysis using analysis univariate For see description descriptive.Research results obtained part big Respondent various sex Woman as many as 62 respondents (63.9%) compared to man with results highest that is level stress currently as many as 83 respondents (83.6%) from the source from coercion self and react to behavior.A total of 83 students experience stress level while the source is from coercion self and react stress to behavior. Share student For can more active in look for information or high insight to avoid​ from stress academic in finish task end thesis.